2013
DOI: 10.1007/s11102-013-0506-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatments, complications, and healthcare utilization associated with acromegaly: a study in two large United States databases

Abstract: The economic burden of acromegaly in the US has been largely unknown. We describe the prevalence of treatment patterns, complication rates, and associated healthcare utilization and costs of acromegaly in the US. Patients were identified between 1/1/2002 and 12/31/2009 in claims databases. During 1-year after each continuously-enrolled patient's first acromegaly claim, pharmacy and medical claims were used to estimate outcomes. Regression models were used to adjust outcomes. There were 2,171 acromegaly patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(70 citation statements)
references
References 15 publications
4
62
2
2
Order By: Relevance
“…The mean age of our cohort was younger than that in most previous reports [5,6,16,17]. The disease activity of GH-producing tumours in patients with acromegaly has been suggested to be associated with visceral adiposity index and insulin sensitivity [18,19]; however, IGF-I correlates more closely than GH with insulin resistance and glucose intolerance [20,21].…”
Section: Discussionmentioning
confidence: 71%
“…The mean age of our cohort was younger than that in most previous reports [5,6,16,17]. The disease activity of GH-producing tumours in patients with acromegaly has been suggested to be associated with visceral adiposity index and insulin sensitivity [18,19]; however, IGF-I correlates more closely than GH with insulin resistance and glucose intolerance [20,21].…”
Section: Discussionmentioning
confidence: 71%
“…In this study, the majority (70%) of patients were currently on treatment, and the vast majority (>90%) of those patients were prescribed SSAs or pegvisomant. Recent claims database studies have also reported SSAs and pegvisomant (collectively) among the most common treatments 8,20,21. All of these treatments are injectable therapies, which can be associated with various patient concerns18 and difficulties in terms of side effects, adherence, and overall impact on QoL;4 these treatments are also associated with substantial costs 7,8.…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of acromegaly, which commonly include fatigue, joint pain, snoring, excessive sweating, and headaches, often interfere with daily life activities 1,4. Acromegaly-related comorbidities and complications (eg, cardiovascular disease, diabetes, cancer, kidney failure, hypothyroidism, bone/joint abnormalities, and sleep apnea)1,59 further contribute to decreased QoL10 and are associated with a high economic burden7,8 and increased mortality risk 11,12…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the disease burden and cost of acromegaly treatment emerge as a considerable topic for acromegaly management. The direct healthcare cost was $24,900 during the first 12 months of follow-up period following diagnosis of acromegaly reported in a cross-sectional cohort study in the USA 3. Very few studies have assessed the impact on the disease burden of acromegaly, especially on treatment satisfaction and indirect costs such as work productivity/employment in the USA.…”
Section: Introductionmentioning
confidence: 99%